Intelligent material handling mobile robot for industrial purpose with active force control capability - Mailah, Musa; Jamaluddin, Hishamuddin; Pitowarno, Endra; Purnomo, Didik Setyo (Universiti Teknologi Malaysia, 2005)
This report presents both theoretical and experimental studies of a wheeled mobile system that incorporates a number of intelligent and robust closed-loop control schemes. The system may actually represent an automated material-handling transporter that can be effectively used in a manufacturing or industrial environment. An integrated kinematic and dynamic control with embedded intelligent algorithms were the main approaches employed for the robust motion control of a mobile manipulator (MM) comprising a differentially driven wheeled mobile base platform with a two-link planar arm mounted on top of the platform. The study emphasizes on the integrated kinematic and dynamic control strategy of the schemes in which the former serving as the outer most control loop is used to manipulate the trajectory components while the latter constituting the inner active force control (AFC) loop is implemented to compensate the dynamic effects including the bounded known or unknown disturbances and uncertainties while the system is executing trajectory tracking tasks. The proposed intelligent schemes considered in the study are the fuzzy logic (FL) and knowledge-based system (KBS) strategies that are incorporated into the AFC schemes to automatically estimate the inertia matrix of the system necessary to trigger the disturbance rejection capability. A virtual mobile system was also designed and included in the study to demonstrate the system capability to operate effectively in a virtual computer integrated manufacturing (CIM) environment. The effectiveness and robustness of the proposed schemes were investigated through a rigorous simulation study and later complemented with experimental results obtained through a number of experiments performed on a fully developed working prototype in a laboratory setting. A number of disturbances in the form of vibratory and impact forces are deliberately introduced into the system to evaluate the system performances. The investigation clearly demonstrates the excellent robustness feature of the proposed control scheme compared to other systems considered in the study.